Soil Texture Effects on Surface Resistance to Bare‐Soil Evaporation. Issue 19 (2nd October 2018) - Lehmann, P.; Merlin, O.; Gentine, P.; Or, D.
Abstract: Modeling of surface energy balance and the separation of evapotranspiration to its component fluxes require quantification of evaporation from land surfaces. The nonlinear relationship between surface heat fluxes and the hydration state of soil surfaces present a challenge to remote estimation of surface evaporation rates. We study the often‐overlooked role of soil properties in determining surface evaporation resistance. We present a framework for quantifying how the ratio of actual to potential evaporation rates varies with changes in surface water content for different soil textures. The model uses the evaporative characteristic length (a soil‐dependent active depth of evaporation) and soil resistance to capillary flow across that region. Predictions were in good agreement with flux tower measurements of bare‐soil evaporation from 10 soil textural classes. The study offers a simple and physically based method for incorporating surface evaporation resistance into land‐surface models considering soil type and surface water content. Plain Language Summary: Water evaporation from soils is an important process of the hydrologic cycle and Earth surface energy balance. The evaporation rates depend on the available energy but are very sensitive as well to the capacity of the soil to retain water and to supply it to the surface where evaporation occurs. This capacity mainly depends on the size of the pores that is related to soil texture. In this letter we present a physically based model that predicts evaporation rates for different textures and soil water contents. The predictions were successfully compared with measurements from various bare‐soil sites around the globe. The presented approach can be applied in land‐surface models and remote sensing estimates. Key Points: Bare‐soil evaporation is a nonlinear function of water content and soil texture that jointly determine capillary water supply rates to vaporization plane at the surface A soil type‐based analytical model for predicting evaporation‐induced capillary flow depth and surface resistance to evaporation was presented Predictions by the resistance model were in good agreement with flux tower evaporation measurements from 10 different soil types across climatic conditions